Distinct and convergent consequences of splice factor mutations in myelodysplastic syndromes. Issue 2 (18th November 2019) - Madan, Vikas; Li, Jia; Zhou, Siqin; Teoh, Weoi Woon; Han, Lin; Meggendorfer, Manja; Malcovati, Luca; Cazzola, Mario; Ogawa, Seishi; Haferlach, Torsten; Yang, Henry; Koeffler, H. Phillip
Abstract: Myelodysplastic syndromes (MDS) are characterized by recurrent somatic alterations often affecting components of RNA splicing machinery. Mutations of splice factors SF3B1, SRSF2, ZRSR2 and U2AF1 occur in >50% of MDS. To assess the impact of spliceosome mutations on splicing and to identify common pathways/genes affected by distinct mutations, we performed RNA‐sequencing of MDS bone marrow samples harboring spliceosome mutations (including hotspot alterations of SF3B1, SRSF2 and U2AF1 ; small deletions of SRSF2 and truncating mutations of ZRSR2 ), and devoid of other common co‐occurring mutations. We uncover the landscape of splicing alterations in each splice factor mutant MDS and demonstrate that small deletions in SRSF2 cause highest number of splicing alterations compared with other spliceosome mutations. Although the mis‐spliced events observed in different splice factor mutations were largely non‐overlapping, a subset of genes, including EZH2, were aberrantly spliced in multiple mutant groups. We also verified aberrant splicing of key genes USP9X, USP24 (deubiquitinating enzymes), LUC7L2 (splice factor) and EED (PRC2 component) in MDS harboring small deletions of SRSF2. Pathway analysis revealed that mis‐spliced genes in different mutant groups were enriched in RNA splicing and transport as well as several signaling cascades, suggesting converging biological consequences downstream of distinct spliceosome mutations. Our study reveals splicing signatures of each splice factor mutation and identifies shared and distinct sets of mis‐spliced genes and affected biological processes in different spliceosome mutant MDS.